REHCARDICARE: A Digital Telerehabilitation Platform for Cardiac Recovery Following a Coronary Artery Bypass Graft - Elvipson Sinaga; Khairunnisa Batubara (Fakultas Ilmu Keperawatan Universitas Indonesia, 2026)
Post-coronary artery bypass graft (CABG) patients often experience decreased cardiac output, which slows recovery and increases the risk of cardiovascular complications. This research and development study evaluated the preliminary effectiveness of the REHCARDICARE application in increasing cardiac output, a key indicator of successful cardiac rehabilitation. The research also assessed user satisfaction to determine the feasibility of broader implementation. The findings can inform further development of the application. The application development used the (Analysis, Design, Development, Implementation, Evaluation) ADDIE model. The study subjects consisted of 30 post-CABG patients purposively selected at the North Sumatra Integrated Heart Center. An application-based resistance and flexibility training intervention was implemented for eight weeks. Data collection and analysis took place two weeks after the intervention was completed. Using a single-group pretest–posttest design, transthoracic Doppler echocardiography was used to measure cardiac output before and after the intervention. Data analysis involved a paired t-test with a significance level of p < 0.05. Cardiac output significantly increased from 4.12 ± 0.55 L/min to 5.28 ± 0.62 L/min (p = 0.001). The feasibility evaluation showed high user satisfaction (87.5 ± 6.8), indicating that REHCARDICARE was perceived as useful and easy to use, with good patient adherence and no significant safety events. Overall, REHCARDICARE demonstrated improved cardiac output after eight weeks and good user acceptance as a digital cardiac rehabilitation tool for post-CABG patients. It is recommended that this application be structurally integrated into the hospital’s cardiac rehabilitation program, that remote monitoring features, and that further tests be conducted using an experimental design with a control group and a larger sample to strengthen the evidence of clinical effectiveness.